Prawne odniesienia państwa do Kościoła greckokatolickiego w II Rzeczypospolitej - Koredczuk, Józef (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
Since Poland regained independence, the ritual of the Greek Catholic Church which was professed by more than 10 % of the population in the second Republic of Poland, made lots of difficulties both for Catholic Church and government authorities and their relations were problematic. Although Greek Catholic Church was the part of Catholic Church, he was unfavourably treated due to political reasons by the government authorities and almost repressed. On the other hand he was not also recommended by the Catholic Church authorities as a result of political reasons. Contradiction between some of the secular and church law principles resulted in additional misunderstandings among both rituals of the Catholic Church. Legal basis of Greek Catholic Church followed from provisions of the March constitution dated 1921. As a result of Concordat agreement signed in 1925 the Greek Catholic Church bacame a part of the Catholic Church – from the 'Brzeska Union' – and his legal status was regulated. Under those agreements Greek Catholics were classified into «religious majority», even though most of them, from nationality point of view, belonged to national minorities. Such legal status resulted in a number of law complications which are the subject of these analysis.
Keywords: Kościół greckokatolicki; II Rzeczpospolita